The role of Plasma Fibrinogen and Uric Acid Levels in relation to Myocardial Infarction risk in patients with the Metabolic Syndrome- Preliminary findings in the Littoral Region of Cameroon (International Journal of Medicine and Medical Sciences, 2011)
Background: Information on relationship between some biomarkers (uric acid and plasma fibrinogen) to the risk of myocardial infarction in patients with the metabolic syndrome among Africans is inexistent or scanty at best. Moreover there is a burden of myocardial infarction and metabolic syndrome on the population. Aims: The objective of this study was to establish the correlation: plasma fibrinogen and uric acid to myocardial infarction risks in patients with the metabolic syndrome. Method— A total 68subjects(34 patients and 34 healthy controls) aged between  18 -80 years    were recruited for this study between November 2010 and  March 2011.Patients for the study as well as the controls were recruited from  Douala  and were matched  for sex ,age and place of residence. Trained nurses, using standard procedures, obtained blood pressure and anthropometric measurements and collected a venous blood sample for assay of plasma fibrinogen and uric acid. Serum uric acid was measured enzymatically after hydrolyzation to glycerol, Plasma glucose concentration was measured using an enzymatic reaction. Plasma fibrinogen was estimated by the Hook’s procedure. Data were analyzed using SPSS version 15 .. Results:   Negative correlations were record between plasma fibrinogen and FBS, height, pulse, WHR and systolic pressure .Uric acid did not show any negative correlation with any of the indicators. There was no correlation between uric acid and fibrinogen (r=-0.056; p=0.599). As for uric acid, it showed very strong correlation   with weight, height, waist circumference, diastolic pressure and body mass index.) Plasma fibrinogen showed the strongest correlation with Hip circumference (r=0.362, p